Recognizing and valuing indigenous knowledge and practices - Kaizo Iwakami Beltrao; Juliane Sachser Angnes (Arizona State University, 2020)
This dossier presents results of studies that glimpse the experiences of indigenous peoples in the task of satisfying their specific needs in indigenous school education and indigenous education, incorporating from that, their history, beliefs, value system and organizational culture. The socio-historical trajectory for indigenous peoples to achieve their pedagogical autonomy involves the appropriation of educational processes that are linked to both indigenous school education and indigenous education (own learning processes). For indigenous peoples, this path might seem simple, at first, due to the new paradigm of indigenous school education that privileges cultural diversity. However as the indigenous people advance towards the achievement of their own conquest projects, they come across several bureaucratic and difficult issues. In this sense, the guidelines presented here do not reflect all the complexity of the scenarios in which the indigenous populations of Brazil and Latin America find themselves, nor the multiple facets that they can assume. However we hope that the studies socialized here can help and expand the reflections, in addition to serving as an invitation for more and more indigenous populations to have visibility in academic scientific circles.